Knowledge, perception of risk of disease, and infection prevention and control practices among healthcare workers and support staff toward COVID-19 in an Ethiopian referral hospital: a cross-sectional survey - Mindaye, Esubalew T.; Assaminew, Bekalu; Tesfay, Goytom K. (International Journal of Infection Control, 2021)
Coronavirus disease 2019 (COVID-19) is a pandemic affecting over 106 million and killing over 2.3 million people. Inadequate knowledge of the disease coupled with scarce or improper use of infection prevention and control (IPC) measures by healthcare workers (HCWs) and support staff may be contributing to the rapid spread of infection. This survey aims to assess knowledge, risk perception, and precaution practices of HCWs and support staff toward COVID-19 under resource-constrained circumstances at a major referral hospital in Ethiopia. An institution-based survey was conducted in April 2020 using 422 subjects selected by stratified random sampling. A five-section survey instrument was distributed, and the collected responses were cleaned and entered into Epi data (v3.1) and exported to SPSS (v.26) for further statistical analysis. The survey found that about 58% of the HCWs and support staff in the hospital appear to have adequate awareness and perceive COVID-19 to be a high-risk disease. Seven out of 10 subjects practice some form of IPC measures. However, the knowledge among allied HCWs and support staff appears to be inadequate. Gender, occupation, and years in service correlated with the level of awareness. Of those surveyed, 78% were concerned about the lack of personal protective equipment and perceived public transportation to be a high-risk factor for the transmission of infection. Additional campaigns may be necessary to reinforce existing knowledge of HCWs, but more emphasis should be geared toward educating allied HCWs and support staff.